Investigation the Effectiveness of Storytelling on Fifth Grade Turkish Students’ Environmental Problems - Fatma Costu; Elif Demirci; Bayram Costu (Journal of Education in Science, Environment and Health)
Even though there are numerous studies on environmental education in the literature, they are limited to investigate the effects of stories. In this context, this research aimed to investigate the views of fifth grade Turkish students concerning environmental problems through storytelling. In accordance with this aim, action research has carried out. The study was conducted with 35 students enrolled in a middle school. Four stories related to different environmental topics were told participants during four weeks. Qualitative data were obtained through focus group interviews supported by data analysis of word association test (WAT). WAT included six key words was applied as pre- and post-WAT. The frequency tables and concept networks were constructed based on WAT results. Participants discussed the effects of environmental problems, the consequences of environmental problems, and environmental protection through focus group interviews. According to the WAT results, students mostly associated “human” with “environmental problem” and “environmental pollution”. They also used of ecological terms increased at the end of intervention.